THU0173 Long term safety and efficacy of filgotinib in a phase 2B open label extension study in patients with rheumatoid arthritis: results up to 144 weeks. (15th June 2017) - Alten, R; Westhovens, R; Kavanaugh, A; Genovese, M; Winthrop, K; Greenwald, M; Ponce, L; Enriquez, F; Stanislavchuk, M; Mazur, M; Spindler, A; Cseuz, R; et al.
Abstract : Background: Filgotinib (GLPG0634, GS-6034) is an oral JAK1 selective inhibitor with a favorable safety and efficacy profile in two 24-week Phase 2b studies as add-on to methotrexate (DARWIN 1) or as monotherapy (DARWIN 2) in patients with active rheumatoid arthritis (RA). Three daily doses were tested (50mg, 100mg or 200mg) in comparison to placebo. Objectives: To assess long term safety and efficacy of filgotinib 200mg daily in patients from the DARWIN 3 Phase 2 open-label extension study. Methods: Patients who completed DARWIN 1 or 2 and enrolled in DARWIN 3 received filgotinib 200mg once daily or 100mg twice daily, depending on prior treatment assignment. The DARWIN 3 data cut off was when the last patient reached extension Week 60. For safety, all data from the first intake of filgotinib in DARWIN 1/2/3 were analysed (up to 144 weeks). Results: 877 patients participated in DARWIN 1 or 2, 790 completed and 739 entered DARWIN 3 from 22 countries (82% females, mean age 53y). 559 patients (75.6%) completed Week 60, 9.3% discontinued due to positive Quantiferon, 7.8% due to other adverse events, 6.8% for other reasons and 0.3% due to insufficient response. Overall exposure to filgotinib was 1314 patient-years (PYE). Treatment-emergent adverse events (157.7/100PYE), serious adverse events (5.3/100PYE) and serious infections (1.9/100PYE) occurred at similar rates compared to the core studies, however infections decreased on a percentage basis from 15% (109/739, W0–12) to 5% (25/549, W85–96). 16 cases of Herpes zoster were reported (1.2/100PYE), 6 cases of malignancy (excl. NMSC) (0.5/100PYE) and 1 case of MACE (0.1/100PYE). There was no active case of tuberculosis. Three fatalities were reported (0.2/100PYE). Mean change from baseline (CFB) at Week 96 and CTCAE toxicity grading in lab parameters of special interest are shown in table 1 . Based on an observed case analysis 84% (505/601), 65% (389/601), 44% (267/601) and 51% (299/587) of patients reached ACR20, ACR50, ACR70 and DAS28(CRP) remission at Week 60 respectively. Conclusions: With 1314 patient-years of exposure, the safety profile of filgotinib appears consistent with that of previously reported double-blind studies and the clinical response appears durable. References: Westhovens R et al. Ann Rheum Dis 2016;0:1–11. Kavanaugh A et al. Ann Rheum Dis 2016;0:1–11. Disclosure of Interest: R. Alten Grant/research support from: Galapagos, R. Westhovens Grant/research support from: Roche, Consultant for: Galapagos, Speakers bureau: BMS, A. Kavanaugh Consultant for: Galapagos, Pfizer, AbbVie, Amgen, Celgene, Janssen, Novartis, Eli Lilly, UCB, M. Genovese Grant/research support from: Abbvie, Eli Lilly, Pfizer, Astellas, Vertex, Consultant for: Galapagos, Gilead, Abbvie, Eli Lilly, Pfizer, Astellas, Vertex, K. Winthrop Grant/research support from: BMS, Pfizer, Consultant for: pfizer, BMS, lilly, Abbvie, Roche, UCB, Galapagos, Amgen, M. Greenwald Grant/research support from: Abbvie, Amgen, Bristol Myers Squibb, Celgene, Galapagos, Gilead, Lilly, Merck, Pfizer, UCB, Consultant for: Lilly, Pfizer, L. Ponce: None declared, F. Enriquez: None declared, M. Stanislavchuk: None declared, M. Mazur: None declared, A. Spindler: None declared, R. Cseuz: None declared, N. Nikulenkova: None declared, M. Glowacka-Kulesz: None declared, I. Szombati: None declared, A. Dudek: None declared, L. Meuleners Employee of: Galapagos NV, C. Tasset Employee of: Galapagos NV, P. Harrison Employee of: Galapagos NV, A. Van der Aa Employee of: Galapagos NV